Effects of lacking alternatives for modern language students that belong to the public relations area to do their community outreach in 2010-2011 - Fermán Melara, Silvia Alexandra
The purpose of this research project is to show aspects of the community outreach made at the UES as a process to graduate from modern language major. In addition, the objetive of this project is to know the effects of lacking alternatives for modern language students that belong to public relations area to do their community outreach in 2010-2011